???? ?????? ????? ????? ??????? ?? ???? ??????? 4.0 ??? ??? 5 (LMS) ??????? ???????? ?????? ???? ????? ?????? - Sultan, Sultan; Atmaja, Dwi Surya; Husein, Sudi Yahya (El-Tsaqafah : Jurnal Jurusan PBA, 2021)
This study aims to reveal creative education through the application of the LearningManagement System (LMS) MODEL as a means of teaching Arabic and principles inchoosing educational methods in the industrial era 4.0. Education in the digital era orwhat is known as the industrial era 4.0 must be accompanied by technology that makesit easier for lecturers and students in the educational process, including Arabic.Researchers obtained data through interviews, observation and documentation, thenanalyzed through a ranking process as follows: data reduction, where in this processthe researcher collected and recorded data, filtered, compiled and focused on mattersrelated to the research topic. Then they present a summary of the data and concludewith a conclusion. The researcher reached the results of the study that theimplementation of the Learning Management System (LMS) MODEL as a method oflearning Arabic in the Department of Arabic Language Education at the IslamicUniversity in general resulted in an increase in students' language skills. In addition,education through the application of the Learning Management System (LMS)MODEL as a means of teaching Arabic accommodates a list space for students todiscuss and send messages and allows them to interact among themselves and betweenstudents and teachers, leading to various interactions towards better language skills,and produce optimal language skill competencies because there are no time and placelimitations in the educational process.